In-Situ Transformation of Li-ABW Zeolites Based on Li-Geopolymer - Huaiyuan Dou; Quan Ye; Yan He; Xuemin Cui (Gels, 2023)
Lithium batteries, as energy storage devices, are playing an increasingly important role in human society. As a result of the low safety of the liquid electrolyte in batteries, more attention has been paid to solid electrolytes. Based on the application of lithium zeolite in a Li-air battery, a non-hydrothermal conversed lithium molecular sieve was prepared. In this paper, in-situ infrared spectroscopy, together with other methods, was used to characterize the transformation process of geopolymer-based zeolite. The results showed that Li/Al = 1.1 and 60 °C were the best transformation conditions for the Li-ABW zeolite. On this basis, the geopolymer was crystallized after 50 min of reaction. This study proves that the formation of geopolymer-based zeolite occurs earlier than the solidification of the geopolymer and shows that the geopolymer is a good precursor for zeolite conversion. At the same time, it comes to the conclusion that the formation of zeolite will have an impact on the geopolymer gel. This article provides a simple preparation process for lithium zeolite, explores the preparation process and mechanism, and provides a theoretical basis for future applications.